Developing a Service-driven Process Tool for Telecommunication Services Software Development - Sulistyo, Selo; Fauziati, Silmi; Hidayah, Indriana; Dewanto , Wahyu (2007)
Technology convergence in the telecom and the IT sectors has led to service convergence. One of the challenges of service engineering is to find practical ways to model service separately, such that service may be composed into well functioning application systems satisfying requirements.